Hope and Exploitation in Commercial Provision of Assisted Reproductive Technologies - Wrigley, Anthony (The Hastings Center report, 2023)
Innovation is a key driver of care provision in assisted reproductive technologies (ART). ART providers offer a range of add-on interventions, aiming to augment standard in vitro fertilization protocols and improve the chances of a live birth. Particularly in the context of commercial provision, an ever-increasing array of add-ons are marketed to ART patients, even when evidence to support them is equivocal. A defining feature of ART is hope—hope that a cycle will lead to a baby or that another test or intervention will make a difference. Yet such hope also leaves ART patients vulnerable in a variety of ways. This article argues that previous attempts to safeguard ART patients have neglected how the use of add-ons in commercial ART can exploit patients’ hopes. Commercial providers of ART should provide add-ons only free of charge, under a suitable research protocol.